ANALISIS MINAT PEMBELIAN DITINJAU DARI VARIASI MENU, PELAYANAN, SERTA KETEPATAN HARGA DI KANTIN TELENG TIMUR - Yonathan Sulistyo Tonung Bela (Fakultas Ekonomi Dan Bisnis Universitas Palangka Raya (UPR), 2022)
This research aims to find out the influence of menu variations, service, and price accuracy on consumer purchasing interests (Study in East Teleng Cafeteria) located in the east teleng street boarding environment No:20X kaliuntu village. This type of research is quantitative research. In this study, researchers used the population as a sample considering the small number in the ability of researchers and the sample taken was 30 people consisting of 15 students and 15 workers based in East Teleng Kost No:20 X Kaliuntu. The data analysis used in this study is Data Validity Test, Data Reliability Test, Multiple Linear Regression Test, Data Normality Test, Data Multicholinearity Test, Data Heteroskedastity Test, Data Autocorring Test, Multiple Correlation Analysis, Data Determination Test, F-Test, T-Test using SPSS (Statistical Product and Service) program version 18.0 for Windows. So thus to maintain the customer's buying interest needs to be done various things, considering the customer is the most important thing for the viability of the business in the future in order to make a profit for the company. And the results of the study can be concluded Product variation, service quality, and price accuracy have a positive effect on buying interest and it is known that the value of t-count > t-table (1,702>1,697) with probability value (( ( = 5%) it means that the hypothesis that states The more variety of products then the increased interest in buying in the canteen teleng timur positive and significant (accepted). Next t-count value> t-table (1,732>1,697) with probability value (( ( = 5%) it means that the hypothesis that states the better the quality of service then the increased interest in buying in the east teleng canteen is positive and significant (accepted). And the last t-count > t-table (3,372>1,697) with probability value (( = 5%) it means that the hypothesis that states The more appropriate the price then the increased interest in buying in the canteen teleng timur positiveand significant (accepted)